DOI: 10.3384/diss.diva-147308
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous material systems for catalysis and drug delivery

Abstract: Hybrid material systems possess multi-functional properties which make them intriguing for the materials science community since very early dates. However, it is not straightforward to produce such material systems. A smart and efficient approach is necessary to extract the desired properties of each component under the desired conditions. This study evolved to its last form primarily around this notion, where the development of a hybrid material is the core of the work. This hybrid material is then further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 206 publications
(458 reference statements)
0
1
0
Order By: Relevance
“…In opposite, methanation is an exothermic reaction equation ( 11) and maximum yield can be achieved in lower temperatures below 400 °C. desorption of the final material [124]. A study revealed that non-porous metal oxide catalysts have low porosity and small specific surface area, which is disadvantageous for absorption and activation of reactant molecules and an ordered mesoporous catalyst has good catalytic activity in CO2 RWGS reaction [125].…”
Section: Manganese Oxide Catalyst For Co2 Hydrogenationmentioning
confidence: 99%
“…In opposite, methanation is an exothermic reaction equation ( 11) and maximum yield can be achieved in lower temperatures below 400 °C. desorption of the final material [124]. A study revealed that non-porous metal oxide catalysts have low porosity and small specific surface area, which is disadvantageous for absorption and activation of reactant molecules and an ordered mesoporous catalyst has good catalytic activity in CO2 RWGS reaction [125].…”
Section: Manganese Oxide Catalyst For Co2 Hydrogenationmentioning
confidence: 99%